1998
DOI: 10.1021/ja980540k
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Radical Formation from the Complexes [Re(R)(CO)3(4,4‘-Me2-bpy)] (R = CH3, CD3, Et, iPr, Bz):  A Nanosecond Time-Resolved Emission, UV−Vis and IR Absorption, and FT-EPR Study

Abstract: Irradiation of the complexes [Re(R)(CO)3(dmb)] (R = CH3, CD3, Et, i Pr, or Bz; dmb = 4,4‘-dimethyl-2,2‘-bipyridine) into their visible absorption band gives rise to a homolytic cleavage of the Re−R bond with formation of the radicals [Re(CO)3(dmb)]• and R•. In the case of R = Et, i Pr, or Bz this reaction proceeds with unit efficiency. The nanosecond time-resolved absorption (TA) spectra show that the long-lived (τ = 7 μs) [Re(CO)3(dmb)]• radicals are formed within the 7 ns la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
65
1

Year Published

1998
1998
2005
2005

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(78 citation statements)
references
References 54 publications
11
65
1
Order By: Relevance
“…For these complexes, nanosecond transient absorption measurements do not show the presence of an excited state precursor, so that bond dissociation must occur within the time period (-7 ns) of the laser pulse. By contrast, in the case of [Re(R)(CO)3(DMB)] (R = methyl) the quantum yields of the reaction in toluene and dichloromethane are 0.4 and 0.7, respectively [7]. In this case flash photolysis measurements do show a transient absorption (lifetime 40 ns in toluene, 35 ns in CH2Cl2) attributed to an excited state with predominant 3MLCT character.…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…For these complexes, nanosecond transient absorption measurements do not show the presence of an excited state precursor, so that bond dissociation must occur within the time period (-7 ns) of the laser pulse. By contrast, in the case of [Re(R)(CO)3(DMB)] (R = methyl) the quantum yields of the reaction in toluene and dichloromethane are 0.4 and 0.7, respectively [7]. In this case flash photolysis measurements do show a transient absorption (lifetime 40 ns in toluene, 35 ns in CH2Cl2) attributed to an excited state with predominant 3MLCT character.…”
Section: Introductionmentioning
confidence: 78%
“…1) and [Ru(E)(R)(CO) 2 (a-diimine)] (II) complexes, where R = alkyl or benzyl, E = I or SnPh3, and a-diimine = 4,4'-dimethyl-2,2'-bipyridine (DMB) or N,N'-diisopropyl-1,4-diazabutadiene (iPr-DAB) have been subject of detailed spectroscopic (UVNis, IR, Raman, NMR, EPR) studies [1][2][3][4][5][6][7]. It has been shown that photoexcitation of these complexes can trigger homolysis of the metal-alkyl (benzyl) bond.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Time-resolved emission spectra of samples in 2-MeTHF glasses (90 K) were recorded in an Oxford Instruments cryostat, using Spectra Physics GCR3 Nd:YAG or Coherent Infinity XPO lasers as excitation sources and an OMA detection system described elsewhere. [62] The solutions were prepared under nitrogen and freezepump-thaw-degassed three times before measurements.…”
Section: Instrumentationmentioning
confidence: 99%